The Effect of Profitability on Firm Value with Dividend Policy as an Intervening Variable in the Banking sector at the Indonesian Stock Exchange (BEI) for the 2022-2024 Period - Wulan Sri Hartati; Maiyaliza; Agustina (Indonesian Journal of Business Analytics, 2026)
The purpose of this study is to examine how profitability affects the value of businesses in the banking industry that are listed on the Indonesia Stock Exchange (IDX) between 2022-2024, using dividend  policy as an intervening variable. The background of this research is based on increasing investor attention to company value amid the dynamics of post-pandemic economic recovery and monetary policy fluctuations. Return on Assets (ROA), Dividend Payout Ratio (DPR) for dividend policy, and Tobin's Q for firm valuation were used to gauge profitability. Using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) and SmartPLS software, this study employed a quantitative methodology. The yearly financial statements of banking firms that were listed on the IDX during the study period served as the secondary data source.  The study's findings demonstrate that a company's worth is positively impacted by profitability. However, dividend policy is negatively impacted by profitability, and company value is negatively impacted by dividend policy. Although their indirect impact is minimal, dividend policies have been demonstrated to moderate the relationship between profitability and firm value. These results are consistent with residual dividend theory and signaling theory, which explain why profitable businesses typically retain earnings for internal purposes in order to sustain long-term growth. In order to boost the firm's value in a sustainable way, this research has significance for investors and company management when deciding on dividend policies and profit management tactics.